Bosnia and Herzegovina Growth and Jobs : Reform Priorities for Promoting Better Private Sector Jobs - World Bank (World Bank, Washington, DC, 2020)
Reducing unemployment and inactivity are urgent priorities for Bosnia and Herzegovina (BiH). Limited job opportunities have fueled emigration, especially among the educated, skilled, and youth. Unlocking Bosnia and Herzegovina’s economic potential requires rebalancing its growth model and boosting the contribution of the private sector to job creation.This report presents the findings of a multisectoral assessment and consultations with entity governments, civil society, and the private sector. Additionally, the report highlights the existing shortcomings in the monitoring of labor market trends and the evaluation of programs.